Arthur Andersen. (C), The collapse of Arthur Andersen - Diermeier, Daniel; Crawford, Robert J.; Snyder, Charlotte ([London] : SAGE, 2016)
The cases describe the demise of Arthur Andersen, a firm that had long set the industry standard for professionalism in accounting and auditing. Once an example of strong corporate culture with a commitment to public service and independent integrity, Andersen saw its culture and standards weaken as it grew explosively and changed its mode of governance.
Originally Published in: Diermeier, D., Crawford, R., & Snyder, C. (2011). Arthur Andersen (C): The Collapse of Arthur Andersen. 5-205-253(C). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Arthur Andersen (Firm); Crisis management -- Case studies; Auditing -- Case studies